Polyphosphate Ester-Type Transporters Improve Antimicrobial Properties of Oxytetracycline - Mariya Kozak; Anna Stasiuk; Vasyl Vlizlo; Dmytro Ostapiv; Yulia Bodnar; Nataliia Kuz'mina; Natalia Figurka; Natalia Nosova; Roman Ostapiv; Igor Kotsumbas; Sergiy Varvarenko; Volodymyr Samaryk (MDPI AG, 2023)
Prolonged use of antibiotics can cause toxicity in human and animal cells and lead to the development of antibiotic resistance. The development of drug delivery systems for enhanced antibacterial properties of antibiotics could reduce toxic effects and minimize the development of resistance. The aim of this study was to evaluate the effectiveness of oxytetracycline in complexes with new polyphosphate ester-type transporters and to investigate the antimicrobial effect of these complexes on Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus growth in vitro. Two polyphosphate ester-type transporters with different molecular weights were synthesized, and oxytetracycline was attached through the phosphorus groups. To determine the sensitivities of microorganisms, oxytetracycline hydrochloride and oxytetracycline complexes with polyphosphate ester-type transporters (P4 and P6) were added to liquid and solid media with E. coli, P. aeruginosa, and S. aureus in different doses. Oxytetracycline in complex with polyphosphate ester-type transporters at low doses (2.3 to 3.8 μg/disk or μg/mL) in both solid and liquid media inhibits the growth of S. aureus more effectively than oxytetracycline alone. The maximum influence on E. coli growth on solid media is observed at a dose of 8 μg/disk of oxytetracycline in combination with both P4 and P6 polyphosphate ester-type transporters. P. aeruginosa growth under the influence of oxytetracycline in combination with polyphosphate-ester type transporters in a liquid medium depends on the dose of antibiotic and the day of cultivation.